Sentence comprehension performance in Malay school-age children: a preliminary study - Choong Xiao Ping; Nur Hazirah Zahrin; Yazmin Ahmad Rusli (Penerbit Universiti Kebangsaan Malaysia, 2024)
When children struggle in understanding what they hear, it hinders them from learning optimally, which subsequently impacts their academic performance, and socially, their ability to develop friendships. The aim of the study was to examine children’s ability in comprehending Malay sentences using a newly developed sentence comprehension task comprising of different sentence structures and cognitive demands. A conventional picture-pointing task was administered to 30 typically developing Malay children between the ages of 7;0 and 12;11 years old (Mean age in months = 119.33, SD = 16.09). Sentences consisted of (i) both canonical (subject-verb-object, SVO; subject relative, SR) and non-canonical structures (passives; object relative, OR), which were also (ii) manipulated in low, intermediate, and high cognitive load conditions. Analysis revealed that there were clearer distinctions in performance on the canonical vs. non-canonical sentences for children in the older age group (10;0 to 12;0) compared to the younger group (7;0 to 9;11), with better comprehension on the canonical structures. Both groups showed a developmental increment in comprehension performance from the simpler SVO and SR sentences to more complex passives and ORs. Although children in the older age group performed comparatively better on the canonical sentences across all cognitive loads, all children struggled as the cognitive demands increased from low to high load conditions within the sentences. In speech-language therapy practice, understanding typical developmental patterns helps clinician identify when a child may need support. The study provides valuable information for clinicians working with school-age children to better gauge their sentence comprehension abilities while being mindful of the diverse ways in which language can develop, particularly for those with neurodevelopmental conditions.